The importance of accounting professional’s motivation in relation to teleworking - Leite, Sónia Ruão; Oliveira, Paulo (Advances in Social Sciences Research Journal, 2020)
The various transformations marked by social, economic and political life in the last decades, have given a prominent place to telework in many fields being accounting one of them. In times of uncertainty, many accounting firms have implemented telework arrangements to provide flexibility and support for employees who seek an acceptable balance between career and family. It is also in this scenario that teleworking comes to assume a fundamental role for the development of accounting itself. Teleworking thus arises as a response to the pandemic situation experienced in our country since March 2020, raising the question of the motivation of accounting professionals in the face of adaptation, motivation and experiences related to teleworking. Through an exploratory-descriptive investigation with a qualitative approach based on the application of a scale of motivation for professionals (adapted), it was our intention to assess the levels of motivation expressed by the accounting professionals in view of the change from in person to online attendance (telework) due to the Covid-19 pandemic.